Aktuelles zur Pneumopathologie: Bericht der Arbeitsgemeinschaft Pneumopathologie der Deutschen Gesellschaft für Pathologie = Current issues in pulmonary pathology : report of the working group on pulmonary pathology of the German Society of Pathology - Schnabel, Philipp Albert; Petersen, Iver; Junker, Klaus (Der Pathologe, 2012)
Abstract: The working group on pulmonary pathology of the German Society of Pathology (Deutsche Gesellschaft für Pathologie, DGP) developed very actively in the last year. Apart from the autumn meeting in Heidelberg in 2011 and the sessions at the annual DGP meeting in Berlin it was possible to realize a first publication with support and coauthorship of several members of the working group dealing with the classification of lung adenocarcinoma. In this report the key aspects of the activity related to the following issues are summarized including non-small cell lung carcinoma, neuroendocrine tumors of the lungs, interstitial pulmonary diseases, cell blocks in cytology and banking in thoracic pathology.
First Online: 20 October 2012
Gesehen am 15.06.2018